O LAZER DAS MULHERES NA MESA DE NEGOCIAÇÕES: cartografando o lazer em movimentos sociais de mulheres brasileiras - Cláudia Regina Bonalume (2020)
This investigation delved into the assemblage of leisure within social movements that defend Brazilian women’s rights, here represented by the Brazilian Women Articulation (Articulação de Mulheres Brasileiras – AMB), the World March of Women (WMM), the Union of Brazilian Women (União Brasileira de Mulheres – UBM) and by specific secretariats dedicated to women in the National Confederation of Agricultural Workers (Confederação dos Trabalhadores na Agricultura – CONTAG), the Unified Workers' Central (Central Única dos Trabalhadores – CUT) and the National Union of Students (União Nacional dos Estudantes – UNE). The objective of this research was to map a cartography of the territory analyzing the relationship between women and leisure in the agenda of the aforementioned social movements. The methodology adopted was the bibliographic research, the document analysis (which, in addition to the documentation provided by the six movements, involved the conferences and the National Plan of Policies for Women) and the narratives of the leaders of the Feminist Movements, obtained through semi-structured interviews. The final presentation of the work refers to a negotiating table where agendas are discussed through a round of presentations, conjunctural analysis, daily order, letter of the meeting and evaluation. The relationship was established through the difficulties of placing leisure in the social movements’ agendas, conferences and plans. The connections between our theoretical background, the document analysis and the narratives of the leaders indicate that macro and micropolitical aspects contribute to these difficulties and offer subsidies to map the cartography of the territory. Such aspects are related to the absence of leisure and, at some times, to the way leisure is understood in women’s lives through discussions around: the place and the role of women in society; the amplitude of the identity markers that constitute the segment of women; the working hours experienced by most of women; the time spent taking care of others, which takes time and space for self-care; the excess of concerns imposed by the assumed responsibilities; the amplitude, complexity and subjectivity around the theme “leisure”; the public sphere, with its male and excluding logic; the commercialization of leisure, which interfere in the possibilities of access; and the non-recognition of leisure as a right. As a challenge, I have established an outline that proposes a new assemblage that might lead to a possible becoming of a feminist leisure.